Birth Weight Standard Deviation Score is a Significant Determinant of Serum Urotensin-II Levels at Term-Equivalent Age in Preterm Infants - Ebata, Akio; Nakano, Yuya; Ujiie, Gakuto; Ishii, Yoko; Shimizu, Takeshi; Fujii, Takanari; Mizuno, Katsumi (American Journal of Perinatology, 2020)
Objective Urotensin II (U-II) is a potent vasoconstrictor peptide, and increased U-II levels are associated with atherosclerosis and hypertension in adults. Low birth weight (LBW) infants have higher risks of such diseases in the future. A small number of nephrons is one of possible mechanism underlying these risks in LBW infants, while vascular elasticity and cardiac function might be another important factor. The objective of this study is to evaluate U-II levels in preterm LBW infants at an early stage of life and determine perinatal factors associated with U-II levels.Study Design The study population consisted of 57 preterm LBW infants (26 males and 31 females), including 49 appropriate for gestational age (AGA) and 8 small for gestational age (SGA) infants, born at a gestational age of ≤34 weeks with a mean birth weight of 1,589 g. Serum U-II levels were measured at term-equivalent age to evaluate perinatal factors related to serum U-II levels.Results Preterm SGA infants had significantly higher serum U-II levels than preterm AGA infants at term-equivalent age (p = 0.019). Serum U-II levels in preterm LBW infants at term-equivalent age were inversely correlated with birth weight standard deviation (SD) score in a simple regression analysis (r =  − 0.395, p = 0,002) and the correlation was maintained in the multiple regression analysis.Conclusion Our results indicate that birth weight SD score might be associated with serum U-II levels in preterm LBW infants at term-equivalent age. Further studies are required to determine whether U-II levels at an early stage of life might influence the risk of atherosclerosis and hypertension.Key Points
Keywords: atherosclerosis; birth weight SD score; hypertension; low birth weight infants; preterm infants; small for gestational age; urotensin II